The Effects of Using a Guidance Activities Package to Enhance Chinese Learning Motivation of Grade 10 Students at Ban Chang Kanchanakul Wittaya School in Rayong Province - Suaniam, Arpakorn; Suksawat, Jirasuk; Mekkhachorn, Nitipat (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
This research aims to compare the Chinese learning motivation of an experimental group students before and after using a guidance activities package to enhance Chinese learning motivation. The research also aims to compare the motivation for learning Chinese between the experimental group students who used the guidance activities package, and the control group students who used the information set after the experiment. The research samples were 60 grade 10 students at Ban Chang Kanchanakul Wittaya School, Rayong Province, during the first semester of the 2022 academic year. They were assigned into an experimental group and a control group, each of which consisted of 30 students. Research instruments included: a guidance activities package to enhance Chinese learning motivation; an information set; and a Chinese learning motivation assessment form with 30 items. Statistics used for data analysis were percentage, mean, standard deviation, and t-test. The research revealed that: after using the guidance activities package to enhance Chinese learning motivation, the experimental group students’ post-experiment mean score of Chinese learning motivation was significantly higher than their pre-experiment with a statistical significance of .01; and after the experiment, the post-experiment mean score of Chinese learning motivation of the experimental group students, who used the guidance activities package, was significantly higher than the post-experiment mean score of the control group students, who used the information set at the .01 level of statistical significance.